Leveraging core capabilities and environmental dynamism for food traceability and firm performance in a food supply chain: A moderated mediation model - Mo-xi SONG; Xin YANG Morgan (Journal of Integrative Agriculture, 2019)
This paper develops a moderated mediation model in which the interactive effects of food traceability and environmental dynamism on firm performance are mediated by the core capabilities (operating capabilities and marketing capabilities) in food supply chain context, by invoking the indirect view of organizational learning theory. Our hypotheses were tested using hierarchical regression and bootstrapping methods with a sample of 216 food manufacturing firms in China, and a survey-based, two-informant design was used to collect data. The results revealed that operating and marketing capabilities fully mediate the food traceability-performance link. In addition, environmental dynamism positively moderates the food traceability-core capabilities link. Moreover, it is found that operating and marketing capabilities transform the interactive impacts of environmental dynamism and food traceability into firm performance. Our study offers a fine-grained picture of the essential food traceability-performance link by revealing for the first time that there is an interactive impacts of food traceability and environmental dynamism on firm performance via core capabilities.